Calcaneal fractures: a management dilemma-minimally invasive approach for intra and extra articular calcaneal fractures - M. S., Kawade; H. S., Madan; Khachane, Shailesh; Dhanda, Manjeet Singh (International Journal of Research in Medical Sciences, 2019)
Background: Calcaneal fractures which constitutes 2% of total fractures are frequent and very debilitating if not treated properly. Calcaneal fractures generally affect younger population leading to significant man-days loss(around 2-5 years3) and in-turn leading significant economic burden on the society. The goal of treatment for calcaneal fractures is elimination of pain and restoration of normal foot shape, biomechanics, and walking ability. Wound related complications are common with open surgeries. After open reduction internal fixation with perimeter plates for displaced calcaneal fractures, wound edge necrosis is commonly observed with the extended lateral approach. Because of such high incidence of wound complications in open reduction of calcaneum fractures, minimally invasive approach takes priority over open reduction of these fractures. Methods: The study aimed to evaluate the results of minimally invasive approach for calcaneal fractures. To reduce the operative complications, 30 patients were treated with minimally invasive methods in both extra articular and intra-articular calcaneal fractures and the results were evaluated. All patients were evaluated clinically , functionally and radiologically 3D- CT reconstruction images. Results: All cases were followed up for 2 years at specified intervals. The outcome measures were evaluated by AOFAS scores10 with excellent result in 13 cases and good to fair results in the rest. Operated patients had no wound infection, no skin necrosis, 5 patients had mild subtalar arthrosis and 3 patients complained slight difficulty in wearing shoes. None of them have any gait abnormalities. Conclusions: Our study suggests that the minimally invasive methods will reduce the operative complication rates. The minimally invasive surgical intervention in an expert hand can yield better results with less complication rates.